Experimental Performance Investigation of Low Speed Horizontal Axis Wind Turbine for Direct Driven Generator - Muldi Yuhendri; Juli Sardi; Citra Dewi; Fatimah Hanifah (Journal of Renewable Energy and Environment)
One method to reduce power loss in wind power plants is by using a low-speed generator that can connect directly to a wind turbine without a gearbox. Low-speed generators require significant mechanical torque, necessitating the wind turbine to produce substantial mechanical torque at low speeds. This requirement can be met by increasing the number and size of blades. This paper proposes a low-speed horizontal-axis wind turbine (HAWT) designed to generate substantial mechanical torque, thus suitable for low-speed generators without gearboxes. The HAWT features six fiberglass blades shaped in a NACA 6412 airfoil. Performance evaluation of the HAWT is based on tip speed ratio (TSR) and power coefficient. The turbine's characteristics were experimentally investigated using a low-speed permanent magnet generator (PMG), a boost converter, and an Arduino Uno controller. Parameter values were observed by testing, the HAWT under varying wind speeds and rotor rotation speeds. Wind speed variation was achievedis varied using a blower, while rotor speed was controlled via a boost converter controlled by an Arduino. Experimental results demonstrate the suitability of the HAWT for its intended purpose, achieving. a maximum power coefficient of 0.34 and an optimum TSR of 5.2.